A Novel Electrochemical Sensor Based on A Glassy Carbon Electrode Modified with GO/MnO2 for Simultaneous Determination of Trace Cu(II) and Pb(II) in Environmental Water. Issue 40 (25th October 2019) - Sun, Hongyan; Wang, Chengxiang; Xu, Yongji; Dai, Dongmei; Deng, Xiaoyan; Gao, Hongtao
Abstract: In this study, manganese dioxide hybridized with graphene oxide (GO/MnO2 ) nanocomposite was prepared by a facile synthesis method, which was applied to modify the glassy carbon electrode (GCE) in an electrochemical sensor of Cu(II) and Pb(II) for the first time. The morphology and structure of the nanocomposite were investigated by scanning electron microscopy, transmission electron microscopy and X‐ray diffraction, which exhibited MnO2 had been uniformly attached to the lamellar structure of GO, resulting in more adsorptive sites. Electrochemical properties of GO/MnO2 /GCE were characterized by cyclic voltammetry and electrochemical impedance spectroscopy and the result confirmed GO/MnO2 /GCE had an excellent electrochemical performance. Furthermore, the important factors affecting on the sensor sensitivity, including pH value, deposition potential, deposition time and material proportion were systematically investigated using square wave anodic stripping voltammetry (SWASV). The interferences from other ions on the target ion have also been discussed in this study. Under the optimal conditions, the GO/MnO2 /GCE exhibited the linear ranges of 0.05 ∼ 1 μM for Cu(II) and Pb(II) with the detection limits of 1.67 nM and 3.33 nM, respectively, which was much lower than some electrochemical methods in reported literatures. The work provides a novel, simple and fast method for the simultaneous determination of Cu(II) and Pb(II). Abstract : A novel electrochemical GO/MnO2 /GCE sensor was constructed by a facile synthesis method for simultaneous determination of trace Cu(II) and Pb(II) in environmental water. GO/MnO2 /GCE had an excellent electrochemical performance by using square wave anodic stripping voltammetry (SWASV), which exhibited the linear ranges of 0.05 ∼ 1 μM for Cu(II) and Pb(II) with the detection limits of 1.67 nM and 3.33 nM, respectively.